(untitled) (Swiss Medical Weekly, 2023)
BACKGROUND: Clinical experience has been shown to affect many patient-related outcomes but its impact in the prehospital setting has been little studied. OBJECTIVES:To determine whether rates of discharge at scene, handover to paramedics and supervision are associated with clinical experience. DESIGN, SETTINGS AND PARTICIPANTS: A retrospective study, performed on all prehospital interventions carried out by physicians working in a mobile medical unit (“service mobile d’urgence et de réanimationˮ [SMUR]) at Geneva University Hospitals between 1 January 2010 and 31 December 2019. The main exclusion criteria were phone consultations and major incidents with multiple casualties. EXPOSURE:The exposure was the clinical experience of the prehospital physician at the time of the intervention, in number of years since graduation. OUTCOME MEASURES AND ANALYSIS: The main outcome was the rate of discharge at scene. Secondary outcomes were the rate of handover to paramedics and the need for senior supervision. Outcomes were tabulated and multilevel logistic regression was performed to take into account the cluster effect of physicians. RESULTS: In total, 48,368 adult patients were included in the analysis. The interventions were performed by 219 different physicians, most of whom were male (53.9%) and had graduated in Switzerland (82.7%). At the time of intervention, mean (standard deviation [SD]) level of experience was 5.2 (3.3) years and the median was 4.6 (interquartile range [IQR]: 3.4–6.0). The overall discharge at scene rate was 7.8% with no association between clinical experience and discharge at scene rate. Greater experience was associated with a higher rate of handover to paramedics (adjusted odds ratio [aOR]: 1.17, 95% confidence interval [CI]: 1.13–1.21) and less supervision (aOR: 0.85, 95% CI: 0.82–0.88). CONCLUSION: In this retrospective study, there was no association between level of experience and overall rate of discharge at scene. However, greater clinical experience was associated with higher rates of handover to paramedics and less supervision.